Special Issue "Valorization of Plant-Genetic Resources and Microbial Communities to Cope with Biotic/Abiotic Stress" - (:unkn) unknown (My University, 2026)
Special Issue "Valorization of Plant-Genetic Resources and Microbial Communities to Cope with Biotic/Abiotic Stress" of Agronomy (ISSN 2073-4395; CODEN: ABSGGL), MDPI